A comprehensive investigation of the reaction behaviorial features of coke with different CRIs in the simulated cohesive zone of a blast furnace. - Qing Q Lv; Yong S Tian; Jun L Zhou; Hua W Ren; Guang H Wang (PLoS ONE)
The reaction characteristics and mechanism of coke with different coke reactivity indices (CRIs) in the high-temperature zone of a blast furnace should be fully understood to correctly evaluate the coke quality and optimize ironmaking. In this work, low-CRI coke (coke A) and high-CRI coke (coke B) were charged into a thermogravimetric analyzer to separately study their microstructural changes, gasification characteristics, and reaction mechanism under simulated cohesive zone conditions in a blast furnace. The results show that both coke A and coke B underwent pyrolysis, polycondensation, and graphitization during the heat treatment. The pyrolysis, polycondensation, gasification speed, and dissolution speed rates of coke B were higher than those of coke A. Direct and indirect reduction between sinter and coke occurred in the cohesive zone and had different stages. The consumption rate of coke B was faster than that of coke A during the coke-sinter reduction. The carbon molecules of coke A must absorb more energy to break away from the skeleton than those of coke B.